Answer:
Brother is 3 and Robert is 13
Step-by-step explanation:
R= roberts age
B = brothers age
R = B+10
In 2 years, so we add 2 to each age
(R+2) = 3(B+2)
We now have 2 equations and 2 unknowns
Substitute R = B+10 into the second equation
(B+10+2) = 3(B+2)
Combine like terms
(B+12) =3( B+2)
Distribute the 3
B +12 = 3B+6
Subtract B from each side
B-B +12 = 3B-B+6
12 = 2B+6
Subtract 6 from each side
12-6 = 2B +6-6
6 = 2B
Divide by 2
6/2 = 2B/2
3 =B
Brother is 3
Now we need Roberts age
R = B+10
R = 3+10
R =13